Self-regulation in the structure of personality maturity - Kolchik, Elena Yur’evna (Research Result. Pedagogy and Psychology of Education, 2024)
Introduction. Personal maturity is a multidimensional psychological construct that determines the success of self-realization of a person in society. Self-regulation is the result of social interaction and means arbitrariness in the management of processes of consciousness and behavior. The purpose of the work is to study the features of selfregulation in boys and girls with different levels of personal maturity. Materials and methods. The study involved 54 students aged 20-22 years, including 30 girls and 24 guys studying at the Fevzi Yakubov Crimean Engineering and Pedagogical University, Simferopol. The respondents were offered a methodology for diagnosing personal maturity by V.A. Ruzhenkov, as well as the questionnaire “Style of self-regulation of behavior” by V.I. Morosanov. Results. As a result of the study, it was revealed that boys and girls with a high level of personal maturity are characterized by a high level of selfregulation with a predominance of the component of evaluating results and independence in its structure. Boys and girls with medium and low levels of self-regulation, in the structure of which flexibility and planning come to the fore, are characterized by an average level of personal maturity. Conclusions. Self-regulation is a significant component and, at the same time, the result of personal maturity, which has a social nature and is not the result of only individual experience. In the process of forming personal maturity, independence, tolerance, as well as taking responsibility for oneself, which are developed in the process of interpersonal interaction and are structural components of self-regulation, are of particular importance. Planning, modeling and evaluating the results of their activities are also components of self-regulation, however, they more determine the procedural side of inclusion in society and are characteristic of a lower level of personal maturity.